The figure of the independent learner: on governing by personalization and debt. Issue 6 (2nd November 2021) - Simons, Maarten
ABSTRACT: Taking the European Credit and Transfer System as its departure point, this article describes the (mis)fortunes of the figure of the independent learner. This figure is conceptualized by analyzing the expectations of the European learning space that is enacted in discourses, instruments and practices. The independent learner is a de-institutionalized learner who is permanently in need of qualifications, calculations and mobility, and what takes shape is a 'governing by personalization and debt'. Key components of today's European learning space are no longer disciplinary norms (with inspection) and administrative rules (with sanctions), but personalizing profiles (with feedback). Understanding current forms of governing is of importance in order to perceive that what is appreciated today in terms of liberation and independence is in fact the inscription of the student in new forms of governing. The analysis concludes by raising the question of where university pedagogy begins and governing education should hold off.